Approach-Based Analysis on Wireless Power Transmission for Bio-Implantable Devices - Nithiyanandam, Vijayanandam; Sampath, Vidhya (Applied sciences, 2023)
The wireless power transmission (WPT) is a systematic technology improve many constraints affecting implantable devices. Many methods have been introduced over the years for WPT. In this article, based on different approaches, we discuss and analyze philosophically the recent existing methodologies and techniques for efficient WPT in implantable devices. For each recent powering method or approach, the working principle and their outcomes are mapped. The performance, efficiency, operating frequency and stability of the systems have been highlighted and listed.